Issues that Matter When Behavioral Finance Factors Drive the Largest Initial Public Offering in the Saudi Financial Market - Shaddady, Ali; Alsaggaf, Mohammed (International Journal of Economics and Financial Issues, 2020)
Behavioral financing is an emerging science and a relatively new area for academic research, leveraging investors’ irrational behavior. To a certain degree, most investment decisions are affected by investors’ biases and expectations, which do not follow rationality requirements. This study rigorously investigated a group of behavioral financial factorsâ€”optimism, pessimism, overconfidence, herd behavior, and loyaltyâ€”and firm characteristics, and then it examined whether and to what extent behavioral financial factors drive investors’ behaviors about the largest initial public offerings (IPOs). This study employed structural equation modelling and used a representative survey of 353 investors during the IPO of Saudi Aramco. The study found that the factors that stimulated investors in the Saudi market, especially during the Aramco IPO behavior decision, included behavioral finance factors, such as optimism, overconfidence, loyalty, and herd behavior, while firm characteristics failed to shape investors’ decisions during Aramco’s IPO. Keywords: behavioral financial, firm characteristics, initial public offering, optimism, herd behavior, overconfidence JEL Classifications: G40, G41 DOI: https://doi.org/10.32479/ijefi.10442